Studi Rekonfigurasi Sistem Distribusi Pada Jaringan 20 kV Dengan Metode Simple Branch Exchange Pada Penyulang Cempaka - Fathur Nureza Aksan; Samsurizal (EPSILON: Journal of Electrical Engineering and Information Technology, 2021)
The increasing electric energy consumption must be balanced with good electricity network quality. To overcome this, we need a distribution network reconfiguration. Reconfiguration in power distribution network is done to improve power distribution network quality. Problem that exist in the radial distribution network is power losses. To minimize the power losses can be overcome by compensating capacitor. Done by determining the location of capacitors in distribution networks. With that the capacitor compensates the distribution network is more effective and efficient in distributing power. In this research discusses the network reconfiguration using simple branch exchange method to reduce power losses in radial distribution networks. The reconfiguration method was carried out with the help of the Electrical Transient Analysis Program (ETAP) 12.6.0 software and has been tested by PT REKAYASA INDUSTRI and PLN Area South Kalimantan on the 20 kV distribution system of Cempaka feeder, South Kalimantan. With this reconfiguration, the voltage drop that occurs on several buses, especially bus 37 and 44, has a voltage drop of up to 95.03% to 95.31% with an average drop voltage of 95.1%, which means the average voltage drop. each feeder is ableto send electricity to consumers properly.